Hubungan Personality (Pro-Environmental Behavior) dengan Perilaku Pro-Lingkungan (Pro-Environmental Behavior) Siswa - Datau, Rahmirini (IJEEM - Indonesian Journal of Environmental Education and Management, 2019)
This study aims to discover the correlation between personality and pro-environmental behavior in students, personality is made up of five factors (openness, conscientiousness, extraversion, agreeableness, and neuroticism) that each have its own correlation towards the students moral environmental behavior. This study uses quantitative survey method and involves 89 data samples and was taken in SMAN 27 Jakarta. The data is collected through participant observation using questionnaire. Based on empirical data obtained as a result of this study, personality traits are an important factor that alters pro-environmental behavior in students, especially factors such as conscientiousness.